Assessing the performance of bio compost as soil media in extensive green roof - Fai Chow M.; Bin Ahmad Azlan A.A. (Institute of Physics Publishing, 2023)
Composted green waste is a recycled material which can be produced locally, adding value to the environmental credentials of a green roof system. As the organic component of green roof growing media, composted green waste can contribute positively to the physical requirements as well as improve environmental performance. In addition it can contain nutrients for plant growth and survival. These will not typically be provided by an inert inorganic substrate and will help establish vegetation. This study is aimed to investigate the performance of bio compost as soil media in extensive green roof with respect to different composition. Runoff were tested for total suspended solids (TS), turbidity, chemical oxygen demand (COD), pH, and color measurements. The results showed that 50% of bio compost in soil media has the best performance in term of plant growth and runoff quality. Published under licence by IOP Publishing Ltd.